Meliora : a journal of Barnard English theses - Columbia University. Libraries; Barnard College (Columbia University Libraries, 2021)
Meliora is Barnard College's premier, undergraduate-run, open access literary journal committed to publishing peer-reviewed, original English senior theses on a bi-annual basis.
Keywords: English literature : History and criticism : Periodicals